Analysis of Geographic Environmental Risk Factors Associated with Dengue Infection in Palembang City - Muhammad Prima Cakra Randana; Irfannuddin; Nurhayati Damiri; Chairil Anwar (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2026)
This study aimed to identify the relationship between environmental factors temperature, humidity, and rainfall, and dengue infection incidence in Palembang City, with emphasis on temporal lag effects and their implications for disease surveillance and control. A quantitative descriptive study was conducted using monthly secondary data from 2021 to 2023. Time-series descriptive analysis and lag correlation methods were applied to examine both concurrent and delayed associations between the environmental variables and dengue case counts. While temperature and humidity showed no consistent concurrent association with dengue incidence, rainfall demonstrated a notable lag-1 effect, whereby increased rainfall in a given month was followed by a rise in dengue cases one month later. This temporal pattern suggests that post-rainfall accumulation of standing water may facilitate mosquito breeding and subsequently elevate transmission risk. These findings highlight the importance of incorporating temporal environmental indicators into dengue early warning systems. Integrating rainfall lag patterns into public health monitoring could support more timely and targeted prevention efforts in Palembang and comparable urban settings across Indonesia.